(untitled) - Burton, Jane.; Taylor, Kim (G. Stevens Children's Books, 1989)
Photographs and text depict how fur, feathers, and blubber keep animals warm in cold weather.
Includes index.
Keywords: Animals; Animals; Regulation; Body temperature; Juvenile literature; Juvenile literature; Adaptation (Physiology); Regulation; Body temperature